Single-Molecule Insights Into the Dynamics of Replicative Helicases - Spinks, Richard R.; Spenkelink, Lisanne M.; Dixon, Nicholas E.; van Oijen, Antoine M. (Frontiers in Molecular Biosciences, 2021)
Helicases are molecular motors that translocate along single-stranded DNA and unwind duplex DNA. They rely on the consumption of chemical energy from nucleotide hydrolysis to drive their translocation. Specialized helicases play a critically important role in DNA replication by unwinding DNA at the front of the replication fork. The replicative helicases of the model systems bacteriophages T4 and T7, Escherichia coli and Saccharomyces cerevisiae have been extensively studied and characterized using biochemical methods. While powerful, their averaging over ensembles of molecules and reactions makes it challenging to uncover information related to intermediate states in the unwinding process and the dynamic helicase interactions within the replisome. Here, we describe single-molecule methods that have been developed in the last few decades and discuss the new details that these methods have revealed about replicative helicases. Applying methods such as FRET and optical and magnetic tweezers to individual helicases have made it possible to access the mechanistic aspects of unwinding. It is from these methods that we understand that the replicative helicases studied so far actively translocate and then passively unwind DNA, and that these hexameric enzymes must efficiently coordinate the stepping action of their subunits to achieve unwinding, where the size of each step is prone to variation. Single-molecule fluorescence microscopy methods have made it possible to visualize replicative helicases acting at replication forks and quantify their dynamics using multi-color colocalization, FRAP and FLIP. These fluorescence methods have made it possible to visualize helicases in replication initiation and dissect this intricate protein-assembly process. In a similar manner, single-molecule visualization of fluorescent replicative helicases acting in replication identified that, in contrast to the replicative polymerases, the helicase does not exchange. Instead, the replicative helicase acts as the stable component that serves to anchor the other replication factors to the replisome.